Use FOIL to solve the problem (3x-2)(2x-3) first ?

1 Answer
Feb 9, 2018

Answer:

#6x^2-13x+6# is the final answer :)

Explanation:

There's a shortcut you can use here, known as the " FOIL " method (that stands for F irst, O uter, I nner, L ast.). The product of two binomials is the sum of four simpler products.

The word FOIL is an acronym for the four terms of the product.
# #
# #
# #
enter image source here
# #
# #
# #
Firsts: #" "# #3x\times 2x=6x^2#
Outsides: #" "# #3x\times -3=-9x#
Insides: #" "# #-2\times 2x=-4x#
Lasts: #" "# #-2\times -3=6#
# #
# #

Add all these up, and you'll get the answer:
# #

#=6x^2+(-9x)+(-4x)+6#

#=6x^2-9x-4x+6#

#=6x^2-13x+6#